Impact of Internet Use on Multi-dimensional Health: An Empirical Study Based on CGSS 2017 Data - Han, Junhui; Zhao, Xiaoqiong (Frontiers in Public Health, 2021)
Based on the data of the Chinese General Social Survey (CGSS) in 2017, the paper divides overall health into physical, mental, and social health, using the ordered probit model to examine the impact of Internet use on multi-dimensional health. It then discusses the possible heterogeneity in different groups and underlying mechanism. Results found that using the Internet can increase overall, physical, mental, and social health by 21.3%, 22.8%, 8.31%, and 10.3%, respectively, than not using the Internet. We apply propensity score matching to handle endogenous problems that may be caused by “self-selection bias,” and the conclusion remains robust. Heterogeneity analysis shows that Internet use has more obvious effects on the health of senior high school education or above, better family economic conditions, the elderly, and men. Further analysis of the mediating effect model found that information, leisure, and social preferences are important path mechanisms for Internet use to promote physical, mental, and social health, respectively.